Continuous Flow Desulfurization of a Model Fuel Catalysed by Titanium Functionalized UiO‐66. Issue 9 (5th March 2019) - Piscopo, C. G.; Voellinger, L.; Schwarzer, M.; Polyzoidis, A.; Bošković, D.; Loebbecke, S.
Abstract: The porous material UiO‐66 is one of the most stable MOFs, retaining its properties under a relatively wide range of chemical and physical conditions, making it attractive for post‐synthetic modifications and catalytic applications. A Titanium functionalization of UiO‐66 has been carried out and the synthesized material has been efficiently used as catalyst in the continuous oxidative desulfurization of a model fuel with aqueous H2 O2 . Using dibenzothiophene as sulfur source, only a partial desulfurization has been achieved, nevertheless the functionalized MOF showed better performances compared to the standard UiO‐66. The titanium containing MOF allowed to completely removing thioanisole from the oil phase within only eight minutes. The pore sizes of UiO‐66 are playing an important role in allowing a fast oxidation of the thioanisole compared to dibenzothiophene. Abstract : Pursuing the optimum between material stability and catalytic activity, a crystalline UiO‐66 has been synthesized and post‐synthetically modified adding Ti IV moiety in order to perform the continuous oxidative desulfurization of a model fuel. The prepared catalyst showed satisfactory performances, which are limited to sulphides with dimensions compatible to the pore size of the MOF.